A guide to changing paradigms of glucocorticoid receptor function—a model system for genome regulation and physiology. (18th July 2021) - Vettorazzi, Sabine; Nalbantoglu, Denis; Gebhardt, J. Christof M.; Tuckermann, Jan
Abstract : The glucocorticoid receptor (GR) is a bona fide ligand‐regulated transcription factor. Cloned in the 80s, the GR has become one of the best‐studied and clinically most relevant members of the nuclear receptor superfamily. Cooperative activity of GR with other transcription factors and a plethora of coregulators contribute to the tissue‐ and context‐specific response toward the endogenous and pharmacological glucocorticoids (GCs). Furthermore, nontranscriptional activities in the cytoplasm are emerging as an additional function of GR. Over the past 40 years, the concepts of GR mechanisms of action had been constantly changing. Different methodologies in the pregenomic and genomic era of molecular biological research and recent cutting‐edge technology in single‐cell and single‐molecule analysis are steadily evolving the views, how the GR in particular and transcriptional regulation in general act in physiological and pathological processes. In addition to the development of technologies for GR analysis, the use of model organisms provides insights how the GR in vivo executes GC action in tissue homeostasis, inflammation, and energy metabolism. The model organisms, namely the mouse, but also rats, zebrafish, and recently fruit flies carrying mutations of the GR became a major driving force to analyze the molecular function of GR in disease models. This guide provides an overview of the exciting research and paradigm shifts in the GR field from past to present with a focus on GR transcription factor networks, GR DNA‐binding and single‐cell analysis, and model systems. Abstract : The glucocorticoid receptor (GR) is a bona fide ligand‐regulated transcription factor. Different methodologies in the pregenomic and genomic era of molecular biological research and recent cutting‐edge technology of single‐cell and single‐molecule analysis are steadily evolving the views of GR and chromatin remodeling as well as its dynamic interaction. The impact of these molecular mechanisms of a transcription factor in physiological and pathophysiological processes is analyzed in model organisms.